Utility, promise, and limitations of liquid chromatography‐mass spectrometry‐based therapeutic drug monitoring in precision medicine. (4th November 2021) - Gaspar, Vanessa P.; Ibrahim, Sahar; Zahedi, René P.; Borchers, Christoph H.
Abstract: Therapeutic drug monitoring (TDM) is typically referred to as the measurement of the concentration of drugs in patient blood. Although in the past, TDM was restricted to drugs with a narrow therapeutic range in order to avoid drug toxicity, TDM has recently become a major tool for precision medicine being applied to many more drugs. Through compensating for interindividual differences in a drug's pharmacokinetics, improved dosing of individual patients based on TDM ensures maximum drug effectiveness while minimizing side effects. This is especially relevant for individuals that present a particularly high intervariability in pharmacokinetics, such as newborns, or for critically/severely ill patients. In this article, we will review the applications for and limitations of TDM, discuss for which patients TDM is most beneficial and why, examine which techniques are being used for TDM, and demonstrate how mass spectrometry is increasingly becoming a reliable and convenient alternative for the TDM of different classes of drugs. We will also highlight the advances, challenges, and limitations of the existing repertoire of TDM methods and discuss future opportunities for TDM‐based precision medicine.